Modernism and the Choreographic Imagination - Girdwood, Megan (Edinburgh University Press, 2023)
"This book explores Salome’s quintessential veiled dance through readings of fictional and poetic texts, dramatic productions, dance performances and silent films, arguing for the central place of this dancer – and her many interpreters – to the wider formal and aesthetic contours of modernism. Loïe Fuller, Maud Allan, Oscar Wilde, Ida Rubinstein, Alla Nazimova, Djuna Barnes, Germaine Dulac, Edward Gordon Craig, W. B. Yeats, Ninette de Valois and Samuel Beckett are foregrounded for their innovative engagements with this paradigmatic fin-de-siècle myth, showing how the ephemeral stuff of dance became a constitutive element of the modernist imagination during this period."